Hydration modelling of an ettringite-based binder. (October 2015) - Georgin, J.F.; Prud'homme, E.
Abstract: Aluminous cement, when mixed with calcium sulfate and water, produces a binder called an ettringite binder. A model of the hydration of an ettringite binder that accounts for the reactive surface of the solid phases in a solute was proposed. Mechanisms of precipitation and dissolution were considered. Calibration was performed based on the kinetics of the conductivity of the solute. Experimental pH kinetics are in accordance with the model prediction. Based on this good agreement, the final part of this article discusses the model predictions of the hydration of an ettringite-based binder.